A Cape of Asia Essays on European History - Wesseling, H.L (Leiden University Press, 2011)
A Cape of Asia collects eighteen of Wesseling's finest essays on European History, clustered around three concerns: The Wider View, or the historical European perspective on globalization, migration and decolonization; Europe's Identity, reflecting the shift from Eurocentrism to Americanization and Europe's acceptance of Japan, China and India as new key players in the global economy; and European Ideas about Education, Science, and Art. The third section includes the articles 'Johan Huizinga and the Spirit of the Nineteen Thirties' and 'The Expansion of Europe and the Development of Science and Technology'. A small cape of Asia was how Paul Valéry described Europe in 1919 - a pointed summary of the new mood that came over Europe in the interbellum years. Wesseling's essays hold to the original sense of the word: personal reflections on vast subjects written for an intellectual and interested but not necessarily specialized readership.